PRODUCTION OF FLAVORED LOW FAT PROCESS CHEESE - A. K. Hassan (Mesopotamia Journal of Agriculture)
Whole sheep milk cheese was used to produce processed flavored cheese with 30 % +-1 fat level after mixing with low fat filing materials such as crud. labanah and skim milk powder. as well as cheese emulsifiers of 1:1 sodium phosphate and citrate. Wild garlic. cumin. nigella and cordomon of 1% were used as flavoring materials. Processed cheese samples were subjected to chemical. bacteriological analysis and sensory evaluation. After storage for two months at room and refrigerator temperature. The results showed that fat. moisture and lactose were decrease while total and soluble nitrogen were increased during storage period. Storage at room temperature had a significant effect on the values compared to refrigerant temperature. Results also shoed that flavoring materials had no effect on chemical composition while wild garlic have the effect in preventing the growth of microorganism .cordomon had the lower effect on microorganism . Results also showed that wild garlic was preferable for sensory evaluation. The effect of filling naturals on bacteriological content reverted that labanah had the lightest bacterial content while skim milk powder had the lowest count. On the other hand. using curd in the processed cheese gave the highest scoring evaluation.